Mesolithic-neolithic contacts as reflected in ritual finds - Bánffy, Eszter (Documenta Praehistorica, 2005)
The beginnings of settled life in Central Europe were marked by a series of interactions between local foragers and immigrants of southern origin. The Carpathian Basin is the last region to have had direct contact with Balkan peoples in the early Neolithic. In the course of the interaction, not only did two groups of different origin and manners meet and merge: two ways of symbolic thinking, two kinds of cult life, two perceptions of space and time must have come face to face. We know much more about south-east European Neolithic cults and ritual life, as reconstructed from enormously rich finds of material consisting of figurines, house models, anthropomorphic vessels etc. In the western part of the Carpathian Basin there are local imitations ofthese finds, thanks to contact. However, the figural representations almost entirely disappear bz the developed phase of the Linear Pottery culture in Central Europe. Thus, we maz find some hints about the other, local way of thinking. The possible causes of this change and also different perspectives in the symbolic meaning of this process are discussed in this short paper.
Keywords: arheološke najdbe; mezolitik; neolitik; družbeni razvoj; navade; običaji